Septic Arthritis Presenting as Brachial Plexus Neurophaty - Mascarenhas, A (2013)
Bone and joint infections are rare in the neonatal period. They often present with pseudo paralysis of the affected limb due to pain and discomfort caused by movement. The existence of a concomitant neuropathy is a rare and insuffi ciently understood phenomenon with few cases described. The authors report the case of a 7-week infant, born prematurely and with Staphylococcus aureus neonatal sepsis, who presented to the emergency room with a paretic right upper limb. Osteoarticular infection complicated with brachial plexus neuropathy was considered and MRI and electromyography the confi rmed diagnosis. There was a good outcome after antibiotic treatment and functional rehabilitation.